Hubungan Antara Motivasi Belajar dengan Prestasi Belajar Siswa Kelas X Tata Boga Mata Pelajaran Boga Dasar di SMK Negeri 2 Depok - Duma Damanik (Transformasi Manageria: Journal of Islamic Education Management, 2022)
This study aims to determine: 1) the learning motivation of students in class X Catering Basic Catering Subjects at SMK Negeri 2 Depok; 2) the learning achievement of class X Culinary Administration in Basic Culinary Subjects at SMK Negeri 2 Depok; 3) the relationship between learning motivation and learning achievement of class X students in Basic Catering Subjects at SMK Negeri 2 Depok. This research is a correlation research using a quantitative approach. The population in this study were students of class X Catering Department at SMK Negeri 2 Depok. The sampling technique used was random sampling and the sample size in this study was determined using Isaac and Michael's Table, so the sample in this study was 84 students. Methods of data collection using questionnaires and tests. The instrument trial used validity and reliability tests. The data analysis technique used product moment correlation with the significance level of the analysis results determined at 5%. Based on the results of the study, it can be concluded as follows: 1) the learning motivation of class X students in Basic Catering subjects at SMK Negeri 2 Depok in the sufficient category is 57 students (67.9%), good category is 27 students (32.1%), and (0.0%) in the poor category; 2) the learning achievement of class X students in Basic Catering subjects at SMK Negeri 2 Depok in the good category as many as 77 students (91.7%), sufficient category as many as 7 students (8.3%) and (0.0%) in the poor category , 3) there is a positive and significant relationship between learning motivation and learning achievement of class X Basic Catering Subjects at SMK Negeri 2 Depok, this is evidenced by the value of r arithmetic greater than r table (0.504> 0.213). Thus, there is a relationship between the learning motivation of class X students in the Basic Catering Subject at SMK Negeri 2 Depok. Keywords: Learning Motivation, Learning Achievement